Monetary history, exchange rates and financial markets - Mizen, Paul.; Goodhart, C. A. E. (Charles Albert Eric) (Cheltenham, UK ; Northhampton, MA : Edward Elgar, 2003)
"Monetary History, Exchange Rates and Financial Markets" is a collection of original papers in honour of Charles Goodhart's outstanding contribution to monetary economics and policy. Its contributors provide an insight into an extensive set of issues.
"This volume and its companion have been compiled from the proceedings of a two-day Festschrift conference in honour of Charles Goodhart at the Bank of England, 15-16 November 2001"--Pref.
Includes bibliographical references and index.
oif 22/07/14
Loan
Keywords: Finance -- Congresses; Monetary policy -- History -- Congresses; Foreign exchange rates -- Congresses